(untitled) (Global Journal of Medical Research, 2017)
A study was conducted from October, 2013 to March, 2014 on cattle slaughtered at Assela municipal abattoir with the aim of determining major causes of liver condemnation and to estimate the direct financial losses attributed to the condemned liver. Ante mortem and post mortem inspection procedures were followed throughout the study and abnormalities encountered were recorded. A total of 384 cattle were examined at ante mortem and 9 animals were found to have abnormalities/conditions like lameness, blindness, rough hair, amputated tail and branding. Out of 384 cattle slaughtered, 274 (71.4%) livers were totally condemned. The major causes of liver condemnation were due to hydatidosis (64.6%), fascilosis (20.8%), calcification (7.7%), coinfection of hydatid cyst with fasciola (4.7%), cirrhosis (1.5%) and abscess (0.7%). Comparison of liver condemnation rate was carried out for different age, animal origin and body condition however, statistically significant difference was observed only between age groups.